Organelle Inheritance Control of Mitotic Entry and Progression: Implications for Tissue Homeostasis and Disease - Mascanzoni, Fabiola; Ayala, Inmaculada; Colanzi, Antonino (Frontiers in Cell and Developmental Biology, 2019)
The Golgi complex, in addition to its well-known role in membrane traffic, is also actively involved in the regulation of mitotic entry and progression. In particular, during the G2 phase of the cell cycle, the Golgi ribbon is unlinked into isolated stacks. Importantly, this ribbon cleavage is required for G2/M transition, that a “Golgi mitotic checkpoint” controls the correct segregation of this organelle. Then, after mitosis onset the isolated Golgi stacks are extensively disassembled, and this process is required for spindle formation. Moreover, recent evidence indicates that also proper mitotic segregation of other organelles, such as mitochondria, endosomes and peroxisomes, is required for correct mitotic progression and/or spindle formation. Collectively, these observations imply that in addition to the control of chromosomes segregation, which is required to preserve the genetic information, the cells actively monitor the disassembly and redistribution of subcellular organelles in mitosis. Here, we provide an overview of the major structural reorganization of the Golgi complex and other organelles during G2/M transition and of their regulatory mechanisms, focusing on recent studies that have revealed the fundamental processes that connect organelle inheritance to mitotic progression and spindle formation, and discussing their implications for tissue homeostasis and diseases.